The Effectiveness Test of Aromatic and Flowering Plants in Controlling Thrips sp. Pest Attack on Red Chili (Capsicum annum L): Uji Efektivitas Tanaman Aromatik dan Berbunga dalam Pengendalian Serangan Hama Thrips sp. pada Tanaman Cabai Merah (Capsicum annum L) - Rizkia Dwi A; Nanang Tri Haryadi (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2024)
Cosmos sulphureus and Tagetes erecta are habitats for insects because they are able to provide the food needed by insects in the form of nectar, while the aromatic plants Apium graveolens and Ocimum bassilicum contain essential oils which act as pest repellents. Therefore, these plants can be used as a method of pest control by intercropping with the main crop. This study aims to determine the extent to which the influence of aromatic and flowering plants in controlling Thrips sp. on red chilies. The research was carried out using a randomized block design (RBD) method with one factor studied, namely the effect of aromatic and flowering plants on Thrips sp. pest control on red chili plants and the treatment combination consisted of, P0 = control (Capsicum annum L. without treatment), P1 = (Capsicum annum L. + Apium graveolens), P2 = (Capsicum annum L. + Ocimum bassilicum), P3 = (Capsicum annum L. + Cosmos sulphureus), P4 = (Capsicum annum L. + Tagetes erecta). Analysis of the research data used variance (ANOVA) and if there was a significant difference it was further tested using the LSD (Lessest Significant Difference) level of 5%. The results of this study indicate that the treatment of aromatic Apium graveolens, Ocimum bassilicum, Cosmos sulphurous and Tagetes erecta flowering plants is quite effective in controlling population numbers of Thrips sp. and intensity of attack by Thrips sp. on red chili plants.